Policy responses to rapid climate change: an epistemological critique of dominant approaches - Charlesworth, M; Okereke, C (Elsevier, 2010)
This paper reviews existing policy responses to rapid climate change and examines possible assumptions that underpin those responses. The analysis demonstrates that current policy responses to rapid climate change make unwarranted epistemological and ethical assumptions. Specifically, we argue that the assumptions about the possibility of predicting the climate system including tipping points linked to utilitarian ethical assumptions in the form of cost–benefit analysis are open to contestation and should be subject to global public debate. The paper considers alternative normative approaches and briefly proposes complementary policy responses.